Manajemen strategi dalam meningkatkan daya saing perbankan syariah di era digital - Nurwulandari, Alfina Dwi (Maliki Interdisciplinary Journal, 2025)
The development of digital technology has fundamentally changed the paradigm of the banking industry, including Islamic banking. Digitalization creates significant opportunities to expand financial inclusion, improve operational efficiency, and strengthen competitiveness through service innovations such as mobile banking, digital branding, and fintech integration. However, this transformation also presents challenges in the form of data security, low Islamic financial literacy, and intense competition from conventional banks and fintech companies. This study aims to analyze management strategies that can be implemented by Islamic banks to increase competitiveness in the digital era. The research method uses a descriptive qualitative approach with a literature review of various recent national journals. The results of the study indicate that effective strategies include: (1) implementing digital innovation based on Islamic principles; (2) strengthening digital branding to build public trust; (3) optimizing human resources that are adaptive to technology; and (4) collaboration with fintech and support from government policies. In conclusion, the success of Islamic banking competitiveness in the digital era is largely determined by managerial ability to integrate Islamic values ​​with modern technological innovation.